Genomic Analysis of the Pacific Oyster (Crassostrea gigas) Reveals Possible Conservation of Vertebrate Sex Determination in a Mollusc. Issue 11 (1st November 2014) - Zhang, Na; Xu, Fei; Guo, Ximing
Abstract: Despite the prevalence of sex in animal kingdom, we have only limited understanding of how sex is determined and evolved in many taxa. The mollusc Pacific oyster Crassostrea gigas exhibits complex modes of sexual reproduction that consists of protandric dioecy, sex change, and occasional hermaphroditism. This complex system is controlled by both environmental and genetic factors through unknown molecular mechanisms. In this study, we investigated genes related to sex-determining pathways in C. gigas through transcriptome sequencing and analysis of female and male gonads. Our analysis identified or confirmed novel homologs in the oyster of key sex-determining genes ( SoxH or Sry -like and FoxL2 ) that were thought to be vertebrate-specific. Their expression profile in C. gigas is consistent with conserved roles in sex determination, under a proposed model where a novel testis-determining CgSoxH may serve as a primary regulator, directly or indirectly interacting with a testis-promoting CgDsx and an ovary-promoting CgFoxL2 . Our findings plus previous results suggest that key vertebrate sex-determining genes such as Sry and FoxL2 may not be inventions of vertebrates. The presence of such genes in a mollusc with expression profiles consistent with expected roles in sex determination suggest that sex determination may be deeply conserved in animals, despite rapid evolution of the regulatory pathways that in C. gigas may involve both genetic and environmental factors.